Interfacing Formate Dehydrogenase with Metal Oxides for the Reversible Electrocatalysis and Solar-Driven Reduction of Carbon Dioxide - Miller, Melanie (2019)
The integration of enzymes with synthetic materials allows efficient electrocatalysis and production of solar fuels. Here, we couple formate dehydrogenase (FDH) from Desulfovibrio vulgaris Hildenborough (DvH) to metal oxides for catalytic CO 2 reduction and report an in-depth study of the resulting enzyme–material interface. Protein film voltammetry (PFV) demonstrates the stable binding of FDH on metal-oxide electrodes and reveals the reversible and selective reduction of CO 2 to formate. Quartz crystal microbalance (QCM) and attenuated total reflection infrared (ATR-IR) spectroscopy confirm a high binding affinity for FDH to the TiO 2 surface. Adsorption of FDH on dye-sensitized TiO 2 allows for visible-light-driven CO 2 reduction to formate in the absence of a soluble redox mediator with a turnover frequency (TOF) of 11±1 s −1 . The strong coupling of the enzyme to the semiconductor gives rise to a new benchmark in the selective photoreduction of aqueous CO 2 to formate.